Strategi Guru dalam Melaksanakan Pembelajaran pada Implementasi Kurikulum Merdeka di UPT SD Negeri 009 Sialang Kubang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The implementation of the Independent Curriculum requires teachers to have an adaptive, contextual, and student-centered learning strategy. This study aims to describe teachers' strategies in planning, implementing, and evaluating learning in the implementation of the Independent Curriculum at UPT SD Negeri 009 Sialang Kubang. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that teachers have prepared learning plans through teaching modules that are tailored to the characteristics of students, using various learning methods and media, and implementing student-centered learning. In addition, teachers also carry out diverse assessments, provide constructive feedback, and follow up on learning. These strategies contribute to the creation of an active, conducive learning atmosphere, and support academic development and student character. Teachers play the role of facilitators who encourage students' independence, creativity, and critical thinking skills. The findings of this study show that teacher readiness and school support are important factors in optimizing the implementation of the Independent Curriculum. Therefore, continuous training is needed for teachers so that the learning strategies implemented are more effective and sustainable